Procoagulant Microparticles: New Insights and Opportunities in Pregnancy Loss? - Greer, Ian A. (Thrombosis and Haemostasis, 2001)
In recent years, prothrombotic states have been not only associated with an increased risk of venous thrombosis, but also with pregnancy complications. In particular there is good evidence linking antiphospholipid antibody syndrome, which is associated with increased thrombin generation (1), to recurrent miscarriage. The importance of procoagulant changes in the pathophysiology of recurrent miscarriage is emphasised by the fact that treatment with heparin and low dose aspirin will substantially improve the likelihood of a successful pregnancy (2). Essentially, this is the only successful medical intervention in the treatment of miscarriage. There are also data now accumulating that link congenital thrombophilia to pregnancy complications such as miscarriage, pre-eclampsia, intra-uterine growth restriction, abruption and intrauterine death (3, 4). Furthermore, recent data have shown that acquired changes in the coagulation system, such as the acquired activated protein C resistance of pregnancy is also associated with an increased risk of pre-eclampsia (5). These data collectively suggest that procoagulant changes in general, rather than congenital or acquired thrombophilia in particular are associated with the development of pregnancy complications including fetal loss. However, in the majority of cases of fetal loss no cause is found and we cannot easily link these events to a procoagulant problem in the mother. In this issue of the Thrombosis and Haemostasis, Laude et al. (6) report, for the first time, the association between circulating procoagulant microparticles and pregnancy loss so providing a new insight into potential mechanisms.